KEPASTIAN HUKUM SERTIFIKAT HAK MILIK ATAS TANAH DALAM SENGKETA TERKAIT PUTUSAN HAKIM TERHADAP PERBUATAN MELAWAN HUKUMOLEH BADAN PERTANAHAN NASIONAL - M. Bahrudin; Wira Franciska; Mulyadi Mulyadi (CORPUS JURIS : JURNAL ILMU HUKUM, 2026)
According to Law No. 5 of 1960 concerning Basic Agrarian Principles (known as UUPA), enacted on September 24, 1960, this law serves as the implementation of Article 33, Paragraph (3) of the 1945 Constitution of Indonesia. The UUPA lays the foundation for agrarian law reform to provide legal certainty for the public, thereby preventing land disputes. If certain requirements are not met, the National Land Agency will not issue a land ownership certificate. However, Indonesian citizens still have the right to obtain a legitimate land ownership certificate by gathering evidence and witnesses to strengthen their case, thus persuading the BPN to issue the certificate in accordance with the land and property they rightfully own.In practice, however, there are still many issues related to the National Land Agency reluctance to issue certificates due to various problems. The research questions addressed in this study are: What constitutes unauthorized acts by the National Land Agency in issuing certificates? And what is the legal certainty of land ownership certificates concerning court decisions on unauthorized acts by the National Land Agency? The theories used in this research include the theory of dispute resolution by Yahya Harahap and the theory of legal certainty by Jan Michael Otto.  The research method employed is a normative juridical approach, involving legal literature or secondary data, with sources including primary, secondary, and tertiary legal materials. The research approach used includes legislative, conceptual, analytical, and case study approaches. The technique for collecting legal materials involves identifying and inventorying positive legal rules, literature, books, journals, and other legal sources. The analysis of legal materials is conducted through systematic, grammatical interpretation, and analogical construction.  The results of the research indicate that the resolution of disputes involving unauthorized acts by the National Land Agency, specifically the refusal to issue land ownership certificates, is conducted through litigation by filing a lawsuit against the National Land Agency in the district court. The legal certainty for the original owner of the land ownership certificate, whose request for a new certificate was denied by the National Land Agency, is that they are entitled to a new certificate issuance if there is supporting evidence and witnesses proving the rightful ownership of the certificate. To secure this legal certainty, the original certificate owner must provide concrete evidence and witnesses affirming that the land indeed belongs to them, in accordance with the documents they possess, supporting their legitimate ownership of the land certificate